2022
DOI: 10.3390/agronomy12092228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leaf Surface Roughness and Contact Angle on In Vivo Measurement of Droplet Retention

Abstract: Droplet retention during pesticide application is a serious problem because run-off droplets flow out of the target area and pose a hazard to human health and the environment. The present study was conducted with the aim to measure the droplet retention of sprayed droplets on crop leaves in vivo using a constructed test system. In the measurement, three crop species with different surface properties (tomato, chili pepper, and winter wheat) were selected for droplet retention determination, and the variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The mean contact angle was found to be 91.41° on the right side and 91.66° on the left side. Comparing these results to Ma et al., we observed a reduction in the contact angle on the leaf surface when using our nanoemulsion. This decrease in the contact angle signifies an increase in wettability, leading to higher water retention on the leaf surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean contact angle was found to be 91.41° on the right side and 91.66° on the left side. Comparing these results to Ma et al., we observed a reduction in the contact angle on the leaf surface when using our nanoemulsion. This decrease in the contact angle signifies an increase in wettability, leading to higher water retention on the leaf surface.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle goniometry was conducted to determine the wettability of the nanoemulsion. Ma et al 37 conducted a study on tomato leaves and found that the leaf surface had spike-shaped columns covered in a waxy layer with a density of 36 ± 4 hairs/mm 2 . The contact angle on the tomato leaf surface was measured at 97.67°, indicating a slight hydro- phobicity of the leaves.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The deposition of droplets was affected by components such as microstructure, wax, stomata, and hair on the surface of leaves 56 . The retention of droplets improves in leaves with longer even hairs or rougher surface 57 . Additionally, four types of leaves, namely cocklebur, morning glory, velvet leaf, and coffee senna, showed 99, 77, 65, and 55% of deposition efficiencies, respectively, when sprayed with 140 µm of droplets 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Droplets tend to run off from leaf surfaces during high-volume spraying applications. Moreover, the retention rate of the leaf can be affected by the leaf size, leaf angle, and leaf surface roughness. These properties may change when collectors are placed on leaves. Furthermore, chromatographic paper has strong water absorption properties, which may lead to overestimation of deposition.…”
Section: Discussionmentioning
confidence: 99%